2013
DOI: 10.1177/0020764013503149
|View full text |Cite
|
Sign up to set email alerts
|

Mental health consumer and caregiver perceptions of stigma in Australian community pharmacies

Abstract: Findings provide insight into the stigma of mental illness in community pharmacies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…Indeed, inadequate privacy in pharmacies could impact on consumers’ lack of appreciation for the changed role of community pharmacists. Research with mental health consumers similarly identified a lack of knowledge and/or appreciation amongst some consumers and carers about advanced pharmacy services . A Welsh study investigating the importance of professionalism in pharmacy practice showed clients often lack trust in speaking with pharmacists if there is no privacy …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, inadequate privacy in pharmacies could impact on consumers’ lack of appreciation for the changed role of community pharmacists. Research with mental health consumers similarly identified a lack of knowledge and/or appreciation amongst some consumers and carers about advanced pharmacy services . A Welsh study investigating the importance of professionalism in pharmacy practice showed clients often lack trust in speaking with pharmacists if there is no privacy …”
Section: Discussionmentioning
confidence: 99%
“…We developed a web‐based mental health promotion intervention using the intervention mapping framework . The content, learning techniques and delivery mode for the intervention were informed by a needs assessment undertaken with Australian pharmacy staff and mental health consumers and carers who use community pharmacies . A review of the literature was also undertaken to inform the study and development of questionnaires …”
Section: Methodsmentioning
confidence: 99%
“…Personal consumer narratives, which we incorporated into the intervention materials, are a form of experiential learning technique known to achieve greater impact in reducing stigma than traditional educational approaches such as lectures . Additionally, the intervention incorporated other experiential learning techniques, such as real‐life scenarios and role‐plays, raising awareness of privacy and confidentiality issues, and the impact this can have on stigma (both self‐stigma and social stigma) when not respected, to provide participants with multiple and varied opportunities to interact with the information and improve understanding and confidence . This multifaceted and innovative intervention program was delivered in a flexible web‐based mode with a series of discrete modules proven to enhance accessibility and uptake …”
Section: Methodsmentioning
confidence: 99%
“…This qualitative study was conducted in Queensland, New South Wales and Western Australia in 2011 and 2012 as part of a larger project, with additional findings reported elsewhere . Ethics approval was obtained from a university Human Research Ethics Committee (PHM/13/11/HREC).…”
Section: Methodsmentioning
confidence: 99%